Localized Eruptive Blue Nevi after Herpes Zoster - Fany Colson; Jorge E. Arrese; Arjen F. Nikkels (Karger Publishers, 2016)
A 52-year-old White man presented with a dozen small, well-restricted, punctiform, asymptomatic, blue-gray macules on the left shoulder. A few months earlier, he had been treated with oral acyclovir for herpes zoster (HZ) affecting the left C7-C8 dermatomes. All the blue macules appeared over a short period of time and then remained stable. The patient had not experienced any previous trauma or had tattooing in this anatomical region. The clinical diagnosis suggested blue nevi. Dermatoscopy revealed small, well-limited, dark-blue, compact, homogeneous areas evoking dermal blue nevi. An excisional biopsy was performed and the histological examination confirmed a blue nevus. As far as we are aware of, this is the first report of eruptive blue nevi following HZ, and it should be included in the differential diagnosis of zosteriform dermatoses responding to an isotopic pathway. In addition, a brief review concerning eruptive nevi is presented.